2020
DOI: 10.1002/bmc.4747
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of neonicotinoid insecticide residues in pistachio using a QuEChERS‐based method in combination with HPLC‐UV

Abstract: There is an increasing need to address the potential risks arising from combined exposures to multiple residues from pesticides in the diet. Pesticide residue‐related pollution is a problem that arises because of the increased use of pesticides in agriculture to meet the growing demands of food production. In this study, pesticide residue data were obtained based on an optimized extraction method. For this purpose, we established a method based on quick, easy, cheap, effective, rugged, and safe (QuEChERS) extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Results showed that although the predicted residues exceeded MRLs in some multiple-spraying scenarios, HQ values were consistently below 1, indicating a low health hazard of pesticides for Iranian consumers. These results are in agreement with previous research, which reported no significant risk of neonicotinoid residues via pistachio consumption (Taghizadeh et al 2019;Arabameri et al 2020;Mahdavi et al 2020). Results revealed that average HQ values of all pesticides and all multiple-spraying scenarios were 1.5 and 2 times higher for children compared to teenagers and adults, respectively.…”
Section: Dietary Risk Assessmentsupporting
confidence: 92%
See 3 more Smart Citations
“…Results showed that although the predicted residues exceeded MRLs in some multiple-spraying scenarios, HQ values were consistently below 1, indicating a low health hazard of pesticides for Iranian consumers. These results are in agreement with previous research, which reported no significant risk of neonicotinoid residues via pistachio consumption (Taghizadeh et al 2019;Arabameri et al 2020;Mahdavi et al 2020). Results revealed that average HQ values of all pesticides and all multiple-spraying scenarios were 1.5 and 2 times higher for children compared to teenagers and adults, respectively.…”
Section: Dietary Risk Assessmentsupporting
confidence: 92%
“…Pesticides were extracted from pistachio nuts using a modified QuEChERS method based on Mahdavi et al (2020). For this, representative portions of the sample from each treatment (200 g) were milled and homogenized by a hand blender (Braun MultiQuick 5 Vario MQ5235, Germany).…”
Section: Extraction and Clean-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Several analytical methodologies are commonly employed to detect neonicotinoid residues in food. These include high-performance liquid chromatography with ultraviolet detection (HPLC-UV) [20][21][22][23] , high-performance liquid chromatography-mass spectrometry (HPLC-MS) [24][25][26][27] , ion chromatography (IC) 28 , gas chromatography (GC) 29 , capillary electrophoresis (CE) [30][31][32] , and non-chromatographic methods [33][34][35][36][37] . Overall, among these methods, HPLC-MS is the most commonly used, based on its reliability, sensitivity, and selectivity.…”
Section: Introductionmentioning
confidence: 99%